Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0166229
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ghrelin Concentrations Were Altered with Oestrous Cycle Stage and Increasing Age in Reproductively Competent Wistar Females

Abstract: Changes in appetite occur during the ovarian cycle in female mammals. Research on appetite-regulatory gastrointestinal peptides in females is limited, because reproductive changes in steroid hormones present additional experimental factors to control for. This study aimed to explore possible changes in the orexigenic (appetite-stimulating) gastrointestinal peptide hormone ghrelin during the rodent oestrous cycle. Fed and fasted plasma and stomach tissue samples were taken from female Wistar rats (32–44 weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…This study has also revealed interactions between fed/fasted status and cycle stage on GLP-1 plasma concentrations with increasing age in reproductively competent rats (between 32 and 44 weeks of age), but not on co-secreted PYY. Both fed and fasted total ghrelin (appetite-enhancing) concentrations from these plasma samples [21] were likewise significantly reduced in the slightly older animals. GLP-1 and ghrelin are both involved, in opposing roles, in glucose homeostasis [39].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This study has also revealed interactions between fed/fasted status and cycle stage on GLP-1 plasma concentrations with increasing age in reproductively competent rats (between 32 and 44 weeks of age), but not on co-secreted PYY. Both fed and fasted total ghrelin (appetite-enhancing) concentrations from these plasma samples [21] were likewise significantly reduced in the slightly older animals. GLP-1 and ghrelin are both involved, in opposing roles, in glucose homeostasis [39].…”
Section: Discussionmentioning
confidence: 87%
“…There was no difference in body mass with age (P=0.555).Stomach contents data were analysed against the cycle stage of the preceding day, as the rats were fasted from the beginning of the cull day (from 08.00; before lights off at 11.00), therefore analysis of remaining stomach contents provided an indication of food consumption during the previous day/cycle stage. When fasted from estrus and dissected at metestrus, rats had significantly (F(3, 39)=3.187, P=0.034) more stomach contents (0.96 g) than those fasted from proestrus and dissected at estrus (0.44 g; P=0.028)[21].…”
mentioning
confidence: 95%
“…The d8L dams consumed approximately 250% more than the mean daily food intake of all of the normally cycling nulliparous females (15.5 ± 0.09 g, n=43) used in a prior study (Johnson et al, 2016). Figure 7B) and body mass exceeded that of proestrus control rats (F(7,47)=16.208, P<0.001) by d10L (P=0.038).…”
Section: Peripartum Food Intakementioning
confidence: 88%
“…Fed blood samples were taken from a tail vein, between 12:00 and 13:00 hr, under anaesthesia (isoflurane; IsoFlo, Abbott Laboratories, Maidenhead, UK) to minimise stress during collection, as optimised from an earlier study (Johnson et al, 2016).…”
Section: Blood Collection and Preparationmentioning
confidence: 99%
“…These Wistar females were fully anaesthetised (isoflurane; IsoFlo, Abbott) and decapitated to collect trunk blood and tissue samples for other studies. 15,16 Wistar rats have a gestation period of approximately 21 days, which is slightly shorter than that of Lister-Hooded rats (23 days). Wistar rats were checked regularly close to their expected delivery date (d21 post mating), and cages were carefully checked for pups and counted, without disturbing the dams.…”
Section: Oestrous Cycle Monitoringmentioning
confidence: 96%